Review of the leafhopper genus Riseveinus Li (Hemiptera: Cicadellidae: Evacanthinae), with descriptions of two new species from China - Zhang, Xinmin; Zhang, Yalin; Wei, Cong (Zootaxa, 2010)
The Oriental leafhopper genus Riseveinus Li is redefined with the redescription of its type species Riseveinus sinensis (Jacobi), and descriptions of two new species: Riseveinus asymmetricus sp. nov. and Riseveinus compressus sp. nov. The female genitalia of the species of this genus are described for the first time. One new combination, Riseveinus albiveinus (Li) n. comb., is also proposed. Photographs and a key to all aforementioned species are provided. The relationship of this genus to related genera is discussed.